Characterizing inclusion and exclusion criteria in clinical trials for chimeric antigen receptor (CAR) T-cell therapy among adults with hematologic malignancies. Issue 2 (March 2021) - Jaggers, Jordon L.; Giri, Smith; Klepin, Heidi D.; Wildes, Tanya M.; Olin, Rebecca L.; Artz, Andrew; Wall, Sarah; Jaglowski, Samantha; William, Basem; Benson, Don M.; Rosko, Ashley E.
Abstract: Objective: Restrictive eligibility criteria are a known barrier to patient enrollment into clinical trials. With the introduction of chimeric antigen receptor T-cell (CAR-T) therapy, it is imperative to ensure trials are generalizable to the intended population with appropriate safety guiderails. Methods: Using the U.S. National Library of Medicine's clinical trial database, we identified 84 clinical trials and characterized inclusion/exclusion criteria for CAR-T therapy in hematologic malignancies with a focus on age, performance status, and comorbidities, and the relationship to sponsorship, disease type, and study phase. Results: The overwhelming majority of CAR-T trials imposed restrictions on upper age (n = 54, 64%), performance status (n = 72, 86%), and renal function (n = 76, 90%). Institution-sponsored studies were more likely to have age restrictions (n = 29) than industry-sponsored (n = 20), (83% vs 45%, p < 0.01). There was no relationship between study phase and use of upper age limit restriction or study phase and affiliation with performance status restrictions. Inclusion criteria for renal function was highly variable and ambiguous; creatinine <1.2–3.0 mg/dL, creatinine clearance >20–60 mL/min, and GFR >30–70 mL/min. Conclusion: These results suggest highly variable inclusion/exclusion criteria for early phase CAR-T studies that may limit patient accessibility to therapy and emphasize the need for a standardized, evidence-based approach to patient enrollment.